CARDIOPROTECTIVE EFFECT OF DATE PALM AGAINST DOXORUBICIN-INDUCED CARDIOTOXICITY - Mubarak, Shimaa; Hamid, Shadia Abdel; Farrag, Abdel Razik; Samir, Nahla; Hussein, Jihan Seid (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Doxorubicin (Dox), an anthracycline antibiotic, has been widely used to treat cancer, principally hematological malignancies, and solid tumors. The administration of Dox is a topic of concern in the medical community, as it frequently related to dose-dependent cardiotoxicity. Therefore, the present study was designed to investigate the protective potential of date palm fruit extract on Dox-induced cardiotoxicity. Methods: A total of 40 female albino rats were used in this study and classified into four groups including control, date palm fruit extract, Dox, and treated date palm fruit extract groups. Results: Dox produced a significant increase in creatine kinase-MB and lactate dehydrogenase activities. It also decreased the activities of cardiac glutathione peroxidase and superoxide dismutase but increase levels of cardiac malondialdehyde and also of urinary 8-hydroxy-2-deoxyguanosine. Myocardial toxicity of Dox also appeared in the elevation of serum total cholesterol, triglycerides, and low-density lipoprotein cholesterol levels, while level of high-density lipoprotein cholesterol decreased. Histopathological studies revealed alteration of cardiac tissue structure by Dox. Treatment with date palm fruit extract restored the aforementioned parameters. Conclusion: Date palm fruit exhibits a cardioprotective influence on the heart tissue against toxicity induced by Dox.